Dry Friction Self-Excited Vibrations Analysis and Experiment - Bogacz, R.; Ryczek, B. (Engineering Transactions, 1997)
The paper is devoted to the experimental and theoretical analysis of a set composed of several! degrees of freedom mass-system interacting with a moving belt by means of dry friction. The experimental study allows to formulate the friction model depending on velocity of motion, acceleration, time of adhesion and force rate.